Infected endometriotic cyst due to blunt trauma: a case report - Sujudi, Akmal; Rajuddin (Journal of International Surgery and Clinical Medicine, 2025)
Background: Endometriosis is a common gynecological condition with a prevalence of 2–10% among women of reproductive age. Secondary infection of endometriotic cysts constitutes an uncommon yet potentially severe complication that may arise through multiple mechanisms, including trauma-mediated cyst rupture. Case Presentation: The present case describes a-36-year_old multiparous woman with fever after abdominal massage for chronic pelvic discomfort.. The patient had previously undergone surgery for endometriosis. in 2021 and chronic dysmenorrhea. Physical examination revealed a fixed abdominal mass, and ultrasonography showed an 11.5×9.5×7.9 cm cystic mass with ground glass appearance. Laboratory findings showed elevated leukocytes (29,500 cells/mm³) and CA125 (261 μg/dL). After antibiotic treatment, unilateral salpingo-oophorectomy was performed. Intraoperatively, infected endometriotic cyst with purulent material was found. Conclusion: This case highlights the risk of endometriotic cyst rupture and subsequent infection following abdominal trauma, even from traditional massage therapy. Early detection and appropriate surgical care are critical for good results.